2021
DOI: 10.1111/ddi.13243
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of benthic algae in the South China Sea: Responses to gradually changing environmental factors and ecological impacts on coral communities

Abstract: Aim: In this study, we investigated whether environmental factors can effectively control the spatial distribution of various benthic algae and examined the critical ecological impacts of algae on corals across the South China Sea (SCS). Relationships between benthic algae and environmental factors were assessed, and potential ecological impacts of algae on coral communities were evaluated across spatial scales.Location: A total of 104 sites at 12 coral reefs in four coral reef regions (CRRs) of the SCS (latit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Juvenile corals are good candidates for studying extreme thermal environmental acclimatization (Holbrook et al ., 2018; Liao et al ., 2021). Global corals are rapidly degraded due to local and global disturbance, and juvenile coral recruitment is critical to the persistence and resilience of coral reefs (Albright et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile corals are good candidates for studying extreme thermal environmental acclimatization (Holbrook et al ., 2018; Liao et al ., 2021). Global corals are rapidly degraded due to local and global disturbance, and juvenile coral recruitment is critical to the persistence and resilience of coral reefs (Albright et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The overgrowth of turf algae and the increased in nutrients may disrupt the natural biophysical relationship between macroalgae and environmental factors (Liao et al, 2021). Consequently, although the QDU creates a suitable condition for the growth of macroalgae, they still cannot dominate inshore coral reefs on the east coast of the Hainan Island (Liao et al, 2021). In addition, the QDU and the non-upwelling waters both had very low coverage of calcified algae and coral larvae, far lower the survey in 2010.…”
Section: Benthic Community and Potential Factorsmentioning
confidence: 99%
“…On the other hand, coral reefs along the coast are seriously threatened by eutrophication, fisheries, and other anthropogenic impacts (Alcıvar-Mendoza et al, 2021), all of which reduced the diversity of macroalgae and increase the coverage of turf algae. The overgrowth of turf algae and the increased in nutrients may disrupt the natural biophysical relationship between macroalgae and environmental factors (Liao et al, 2021). Consequently, although the QDU creates a suitable condition for the growth of macroalgae, they still cannot dominate inshore coral reefs on the east coast of the Hainan Island (Liao et al, 2021).…”
Section: Benthic Community and Potential Factorsmentioning
confidence: 99%
“…The low nutrition resistance of COTS larvae may be associated with maternal nutrition (Caballes et al, 2016). Previous studies have shown that the coral cover of Acropora was decreased with the increasing of the latitude in the SCS, and the abundance of Acropora in FTS and PS was higher than that in DI and BR (Zhao et al, 2013(Zhao et al, , 2016Li et al, 2019;Liao et al, 2021). Acropora was as preferred coral prey for COTS, which may provide high quality and quantity of food to female COTS in the FTS and PS, which might promote COTS larvae to tolerate low nutrient availability and to progress to more advanced stages faster (Caballes et al, 2016).…”
Section: Genetic Differentiation Of Crown-of-thorns Starfish Populations May Be Shaped By Distinct Nutrient Concentration In the South Chmentioning
confidence: 99%